Heart rate variability responses to acute and repeated postexercise sauna in trained cyclists - Leicht, A. S.; Halliday, A.; Sinclair, W. H.; D`Auria, S.; Buchheit, M.; Kenny, G. P.; Stanley, J. (Applied Physiology, Nutrition, and Metabolism, 2018)
Short- to medium-term (i.e., 4-14 days) heating protocols induce physiological adaptations including improved cardiac autonomic modulations, as assessed using heart rate variability, which may contribute to greater exercise performance. Whether similar cardiac autonomic changes occur during an intense heating protocol (sauna) reported to increase plasma volume in athletes remains to be confirmed. This study examined changes in heart rate and its variability during a single extreme heat (sauna) exposure and repeated exposures in athletes. Six well-trained male cyclists undertook sauna bathing (30 min, 87 °C, 11% relative humidity) immediately after normal training over 10 consecutive days. Heart rate recordings were obtained during each sauna bout. Heart rate and its variability (natural logarithm of root mean square of successive differences, lnRMSSD) were analysed during 10-min periods within the first bout, and changes in heart rate and lnRMSSD were analysed during each bout via magnitude-based inferences. During the first sauna bout, heart rate was almost certainly increased (~32%, effect size 1.68) and lnRMSSD was almost certainly reduced (~62%, effect size -5.21) from the first to the last 10-min period, indicating reduced parasympathetic and (or) enhanced sympathetic modulations. Acute exposure to extreme heat stress via sauna produced alterations in heart rate and cardiac autonomic modulations with successive postexercise heat exposures producing unclear changes over a 10-day period. The physiological benefits of intense heating via sauna on cardiac control in athletes remain to be elucidated.